Hot-Melt Extruded Amorphous Solid Dispersion for Solubility, Stability, and Bioavailability Enhancement of Telmisartan - Bhupendra Raj Giri; Jaewook Kwon; Anh Q. Vo; Ajinkya M. Bhagurkar; Suresh Bandari; Dong Wuk Kim (MDPI AG, 2021)
Telmisartan (TEL, an antihypertensive drug) belongs to Class II of the Biopharmaceutical Classification System (BCS) because of its poor aqueous solubility. In this study, we enhanced the solubility, bioavailability, and stability of TEL through the fabrication of TEL-loaded pH-modulated solid dispersion (TEL pHM-SD) using hot-melt extrusion (HME) technology. We prepared different TEL pHM-SD formulations by varying the ratio of the drug (TEL, 10-60% w/w), the hydrophilic polymer (Soluplus®, 30-90% w/w), and pH-modifier (sodium carbonate, 0-10% w/w). More so, the tablets prepared from an optimized formulation (F8) showed a strikingly improved in vitro dissolution profile (~30-fold) compared to the free drug tablets. The conversion of crystalline TEL to its amorphous state is observed through solid-state characterizations. During the stability study, F8 tablets had a better stability profile compared to the commercial product with F8, showing higher drug content, low moisture content, and negligible physical changes. Moreover, compared to the TEL powder, in vivo pharmacokinetic studies in rats showed superior pharmacokinetic parameters, with maximum serum concentration (Cmax) and area under the drug concentration-time curve (AUC0-∞) of the TEL pHM-SD formulation increasing by 6.61- and 5.37-fold, respectively. Collectively, the results from the current study showed that the inclusion of a hydrophilic polymer, pH modulator, and the amorphization of crystalline drugs in solid dispersion prepared by HME can be an effective strategy to improve the solubility and bioavailability of hydrophobic drugs without compromising the drug's physical stability.